Medical translation is an art of science - Sheliyna, S. (University of Jaffna, 2018)
Translation is an important factor in spread out the new knowledge and discoveries in the field of science particularly in medical field. Therefore it is called as the art of science. The translators of medical texts face a number of challenges. They include contextual problems, linguistic problems, equivalence etc. This research offers a general overview of the major issues in medical translation. It presents the brief history of medical translation. It also discusses certain characteristic features of medical language and will give a clear idea about translating medical articles in an effective way.
Keywords: Medical translation; Experts; Semi-experts; Laymen; Abbreviations; Accuracy; Medical terminology